Dampak Teknologi Informasi Dan Pentingnya Protokol Kesehatan Bagi Anak-Anak - Ferry Cahaya, Yohanes; Wahyuningisih, Erna; Salim, Agus; Agung, Leo; Simroangkir, Panubut; Safaria, Siti; Prowanta, Embun; Ovalia; Abdullah Alwyni, Farouk (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2022)
One form of the Tri Dharma of Higher Education is to do community service. Community service activities are carried out with the aim of being able to provide benefits and positive impacts for the community, both short term and long term. On this occasion, our group of 7 Perbanas Institute lecturer teams collaborated with students to carry out community service activities at the Mizan Amanah Tebet orphanage, South Jakarta. The activities carried out are providing education, socializing about the benefits and impacts of using the internet for children in learning, as well as preparing health protocols for face-to-face learning. On this occasion we also provided compensation for the students at the Mizan Amanah Orphanage, Tebet Jakarta. We hope that this community service activity will have a positive impact on students in applying the use of the internet and how they can equip themselves to take part in face-to-face learning during this pandemic.